Statistical Literacy as an Aspect of Media Literacy - Poljičak Sušec, Martina; Jerak Muravec, Nevena; Stančić, Hrvoje (2014)
Statistical literacy represents an aspect of media literacy, especially due to a growing share of the statistical information in media reporting. Being statistically literate means being able to correctly interpret and correctly use statistical information available either through the media or through services of official statistics, for the purpose of personal development and direct or indirect effects on the development of institutions and the state. Statistical information provide an overview of the situation in different domains enabling tracking changes in phenomena during time and should be the basis for decision- making in economic, political, cultural and personal sphere of life. Paper analyse the level of development of segmented approach to advancing statistical literacy through the introduction of new statistical media services for educating and informing citizens in Croatia. Development approach for statistical literacy in Croatia is compared with the situation in other countries in Europe and beyond. Authors examine four approaches to the design of media information services which they consider essential in the development of so- called new statistical media services for citizens: nonlinearity, interaction, contextual design and service’s repository openness. Furthermore, authors analyse applications of four development approaches to statistical services for citizens in different contexts thus demonstrating justification of using these approaches for implementation of long-term development strategies of national statistical literacy.
ENG